2010
DOI: 10.1038/sj.bjc.6605554
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of ERG, ETV1 and PTEN gene loci identifies patients at low and high risk of death from prostate cancer

Abstract: BACKGROUND: The discovery of ERG/ETV1 gene rearrangements and PTEN gene loss warrants investigation in a mechanism-based prognostic classification of prostate cancer (PCa). The study objective was to evaluate the potential clinical significance and natural history of different disease categories by combining ERG/ETV1 gene rearrangements and PTEN gene loss status. METHODS: We utilised fluorescence in situ hybridisation (FISH) assays to detect PTEN gene loss and ERG/ETV1 gene rearrangements in 308 conservativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
187
3
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(203 citation statements)
references
References 36 publications
(41 reference statements)
10
187
3
2
Order By: Relevance
“…Recently, we and others have confirmed significant association between ERG rearrangements and PTEN deletions in localized and metastatic/hormone refractory disease. 15,16,19 This observation was also supported by in-vivo studies using transgenic mouse models demonstrating that double transgenic mice for aberrant ERG and PTEN deletions develop frank invasive prostate cancer vs. high grade prostatic intraepithelial neoplasia (HGPIN) in either PTEN deletions or TMPRSS2-ERG gene fusion (the most common form of ERG rearrangement). These murine studies underscore the potential value of PTEN and ERG as early biomarkers of progression in human PCA.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Recently, we and others have confirmed significant association between ERG rearrangements and PTEN deletions in localized and metastatic/hormone refractory disease. 15,16,19 This observation was also supported by in-vivo studies using transgenic mouse models demonstrating that double transgenic mice for aberrant ERG and PTEN deletions develop frank invasive prostate cancer vs. high grade prostatic intraepithelial neoplasia (HGPIN) in either PTEN deletions or TMPRSS2-ERG gene fusion (the most common form of ERG rearrangement). These murine studies underscore the potential value of PTEN and ERG as early biomarkers of progression in human PCA.…”
Section: Discussionmentioning
confidence: 82%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] More recently, several studies demonstrated significant association between ERG rearrangements and PTEN genomic deletions in localized PCA with prognostic implications. [15][16][17][18][19][20] Moreover, studies in transgenic mouse models confirmed that both aberrant expression of ERG and deletion of PTEN are required to develop frank invasive carcinoma, indicating that both genetic aberrations play an important role in driving prostate cancer development and progression. More comprehensive studies are, however required to determine the prognostic significance of these biomarkers for the future clinical management of PCA.…”
Section: Introductionmentioning
confidence: 97%
“…TMPRSS2 rearrangements seem to be reproducibly associated with a less favorable prognosis only when accompanied by PTEN loss. 14,39 The present study was not designed to further assess the association between PTEN deletions, TMPRSS2-ERG rearrangements and clinical outcome. Rather, the aim was to define the incidence of heterogeneity for PTEN deletions and TMPRSS2-ERG fusion rearrangements within and between separate cancer foci in the same prostate, and to determine whether there was any association with modified Gleason pattern.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] PTEN deletions are found in approximately 40% of localized prostate cancers. 8,14,[31][32][33][34][35][36][37][38][39][40][41][42][43][44] In advanced disease, fluorescence in situ hybridization (FISH) has identified hemizygous (loss of one copy) and homozygous (loss of both copies) PTEN deletions, 31,39,43,45,46 with the incidence of PTEN deletion approaching 70-80% of castrate-resistant tumors. 33,40,42,43 It has been shown that hemizygous PTEN deletions are associated with earlier biochemical relapse.…”
mentioning
confidence: 99%
See 1 more Smart Citation